The implications of starvation induced psychological changes for the ethical treatment of hunger strikers - Fessler, D. M. T. (Journal of medical ethics, 2003)
Objective: To evaluate existing ethical guidelines for the treatment of hunger strikers in light of findings on psychological changes that accompany the cessation of food intake. Design: Electronic databases were searched for (a) editorials and ethical proclamations on hunger strikers and their treatment; (b) studies of voluntary and involuntary starvation, and (c) legal cases pertaining to hunger striking. Additional studies were gathered in a snowball fashion from the published material cited in these databases. Material was included if it (a) provided ethical or legal guidelines; (b) shed light on psychological changes accompanying starvation, or (c) illustrated the practice of hunger striking. Authors’ observations, opinions, and conclusions were noted. Conclusions: Although the heterogeneous nature of the sources precluded statistical analysis, starvation appears to be accompanied by marked psychological changes. Some changes clearly impair competence, in which case physicians are advised to follow advance directives obtained early in the hunger strike. More problematic are increases in impulsivity and aggressivity, changes which, while not impairing competence, enhance the likelihood that patients will starve themselves to death.